2016
DOI: 10.1096/fj.201500088r
|View full text |Cite
|
Sign up to set email alerts
|

Role of chemokine RANTES in the regulation of perivascular inflammation, T‐cell accumulation, and vascular dysfunction in hypertension

Abstract: Recent studies have emphasized the role of perivascular inflammation in cardiovascular disease. We studied mechanisms of perivascular leukocyte infiltration in angiotensin II (Ang II)-induced hypertension and their links to vascular dysfunction. Chronic Ang II infusion in mice increased immune cell content of T cells (255 ± 130 to 1664 ± 349 cells/mg; P < 0.01), M1 and M2 macrophages, and dendritic cells in perivascular adipose tissue. In particular, the content of T lymphocytes bearing CC chemokine receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
223
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 211 publications
(241 citation statements)
references
References 42 publications
10
223
1
7
Order By: Relevance
“…T cell SGK1 deficiency prevents Ang II-induced vascular and renal inflammation. We and others have shown that Ang II increases total leukocyte and T cell infiltration into the perivascular fat and kidneys, and that this is likely an important causal factor for the progression of hypertension and the development of end-organ damage (4,14,15). To determine the role of T cell SGK1 on vascular and renal inflammation, we performed flow cytometry on single-cell suspensions of the thoracic aorta and kidney following 7 and 28 days of Ang II infusion in SGK1 (B-D) Summary data of absolute numbers of indicated cell types per thoracic aorta.…”
Section: T Cell Sgk1 Deficiency Attenuates Ang Ii-induced Hypertensionmentioning
confidence: 95%
“…T cell SGK1 deficiency prevents Ang II-induced vascular and renal inflammation. We and others have shown that Ang II increases total leukocyte and T cell infiltration into the perivascular fat and kidneys, and that this is likely an important causal factor for the progression of hypertension and the development of end-organ damage (4,14,15). To determine the role of T cell SGK1 on vascular and renal inflammation, we performed flow cytometry on single-cell suspensions of the thoracic aorta and kidney following 7 and 28 days of Ang II infusion in SGK1 (B-D) Summary data of absolute numbers of indicated cell types per thoracic aorta.…”
Section: T Cell Sgk1 Deficiency Attenuates Ang Ii-induced Hypertensionmentioning
confidence: 95%
“…17,[67][68][69][70] Oxidative stress is central in the pathology both as an initiator of vascular and renal inflammation and the consequence of inflammatory responses and cytokines. [71][72][73] This is particularly important, in light of the role of immunosenescent T cells in hypertension and the susceptibility of T cells to changes associated with aging. 74 They are characterized by loss of CD28 marker and appearance of CD57 and functionally produce tumor necrosis factor-α and interferon-γ, which affect vascular changes.…”
Section: Inflammatory Mechanisms Of Hypertension Are Linked To Oxidatmentioning
confidence: 99%
“…14 Stiffness, vascular resistance, remodeling, and endothelial dysfunction are hallmarks of hypertension. 15,16 The clinical relevance of a non-dipping status in hypertensive patients increases the risk for cardiovascular events. 17 The endothelium-dependent vasodilatation is much more impaired in non-dippers.…”
Section: Discussionmentioning
confidence: 99%